2006
DOI: 10.1038/sj.ejcn.1602429
|View full text |Cite
|
Sign up to set email alerts
|

Iron status and its association with pregnancy outcome in Korean pregnant women

Abstract: Objective: The purpose of this study was to assess the prevalence of iron deficiency anemia among Korean pregnant women and to assess the association between maternal hemoglobin (Hb) level and pregnancy outcome. Design: A longitudinal study. Setting: Ewha Womans University Hospital, Seoul, Korea. Subjects: A total of 248 normal pregnant women of 24-28 weeks gestation and 190 babies born to the pregnant subjects. Methods: Maternal anthropometry, blood parameters and pregnancy outcomes were measured. Results: Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 26 publications
5
54
0
6
Order By: Relevance
“…Epidemiological studies have shown that maternal iron deficiency is associated with increased incidence of IUGR (141,142) . Large placental weights and a high ratio of placental weight to birth-weight are observed (143) .…”
Section: Maternal Iron Restrictionmentioning
confidence: 99%
“…Epidemiological studies have shown that maternal iron deficiency is associated with increased incidence of IUGR (141,142) . Large placental weights and a high ratio of placental weight to birth-weight are observed (143) .…”
Section: Maternal Iron Restrictionmentioning
confidence: 99%
“…3,4 The prevalence of anemia and micromineral-vitamin deficiencies in pregnant women differs considerably depending on their lifestyle and cultural and socioeconomic status. 5 Previous controlled randomized studies have identified important improvements in pregnancy outcomes after the utilization of a supplemental diet. 6,7 In some developed countries, over-Between 20 and 30 percent of pregnant women suffer from at least one kind of vitamin deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…A review of longitudinal studies indicated that children who were anaemic in early childhood continued to have poor cognition and school performance in middle childhood, compared with nonanaemic children 5 . Severe anaemia during pregnancy is strongly related to increased risks of low birth weight, preterm birth and perinatal mortality 6,7 . Iron deficiency, even without anaemia, is also associated with reduced physical performance and work capacity 8 .…”
mentioning
confidence: 99%
“…Common causes of anaemia, other than iron deficiency, include other vitamin deficiencies (e.g. vitamin B 12 , B 6 , folate and C) 4 . Anaemia of chronic disease, a condition accompanied by inflammation, is present in some people, including young children 4 .…”
mentioning
confidence: 99%